Da legislação ao cotidiano escolar: o olhar dos educadores de uma escola pública sobre gestão democrática - Tramontina, Carla Cristine (2020)
Constructing a quality public school is a daily battle for everyone involved in education. This process necessarily involves democratic actions and for this reason, it has become the focus of study and the construction of educational laws and policies. Based on these findings, the present research had a general objective to identify, from the understanding of the teachers in a school of public education system from the municipality of Marau/RS, the way they perceive the democratic management in their workplace. The investigation was guided by the following questions: What is the comprehension of the democratic management carried out by the educators that work in the municipal public school? What actions are possible to implement to build a democratic process in it? The research was developed through a questionnaire and an interview, with teachers as subjects of the investigation. The questionnaire was sent for 50 teachers, which 31 answered and the interview was conducted with 10 participants, selected by the following criteria: those who assumed management positions; those who had never had the opportunity to be a manager; those who work in private, state and municipal schools, concurrently, and a teacher who was a manager, a municipal secretary of education and a city councilor. The methodology used was bibliographic, documentary and field, carried out through questionnaires and interviews, comparing the answers with the theory and interpreting the researched elements. The authors Libâneo (2018), Paro (2000, 2007, 2015), Souza (2009), among others, contributed to elucidate and build the present work, which is divided into six chapters. First, a contextualization of the theme was developed. In the second chapter, a look at democratic management in legislation was made, such as the Federal Constitution, Law Guideline and Bases 9394/96, National Education Plan, Municipal Education Plan and the Pedagogical Political Project of the researched school. In the third chapter, it was studied the organization of the democratic management, reflecting about its conception and principles - participation, democracy and autonomy – trying to understand the manager and the teacher function. In the fourth chapter, the methodology was presented and, in the fifth one, the questionnaires and interviews analyses. The research carried out points to the following results: teachers have a certain level of comprehension about the democratic management, because they pointed out the elements that constitute it, among them: dialogue, decision-making, involvement in actions, commitment, valuing everyone, participation, shared power and horizontal relationships; there is a certain level of critical reflection about those aspects that the school lacks to implement a participatory democratic process, such as: delay in decisions, non-acceptance of opinions, divergence of ideas and lack of knowledge; the surveyed understanding is closely linked to their own participation, with little attention to the employees, students and parents as members that participate in the democratic management processes; it is still necessary to improve the democratic and participatory management process, because it requires the commitment of all in favor of a more humane and fair school for all.